Assessing the Effectiveness of Play-Way and Structural Approaches in the Teaching of English Grammar among Selected Creche Schools in Ijebu-Ode Township - نوكوبوروك إميكان (Jordan Journal of Educational Sciences, 2025)
Objectives: This study set out to compare the effectiveness of the Play-Way and Structural Approaches in the teaching of English language grammar to young learners in selected crèche schools in Ijebu-Ode township. Methodology: The study employed a quasi-experimental design. Two groups of fifteen pupils each, were selected using a purposive sampling technique. However, in a lesson which lasted for four weeks, pupils in the first group were taught aspects of the English grammar using the Play-Way Approach – an approach that emphasises play-oriented instructional methods. Similarly, others were also taught using the Structural Approach - an approach that focuses on grammar rules and structures. Consequently, the effectiveness of both approaches was assessed through pre-test and post-test evaluations. Results: Findings revealed that the Structural Approach was more effective for teaching English grammar to crèche students in Ijebu-Ode township compared to the Play-Way Approach. While the Structural Approach demonstrated greater effectiveness in improving grammar proficiency among young learners in this study, the Play-Way Approach still held potential for other aspects of language learning, such as motivation and engagement. Conclusion: Therefore, on this premise, the study concluded by recommending that a combined teaching strategy that integrates the systematic framework of the Structural Approach with the creativity and engagement of the Play-Way Method be adopted going forward. Regardless of that, the success of such approaches also depends on adequate resources and teacher training to create effective learning environments. Keywords: Creativity, Faculty Staff, Heads of Departments, Jordanian Universities, University Deans.